peran media sosial bagi advokat muda - Hanum, Roro; Midia, Fredy Ghandi; Putri, Amelia Jaya; Farhan, Shandra Fadia (Siyasah, 2024)
In the utilization of social media, there are notable advantages and disadvantages associated with the dissemination of legal information. Unreliable online news platforms have the potential to propagate misinformation, posing harm to society. Nonetheless, legal practitioners can leverage social media as a conduit for dependable legal information by implementing strategic measures. The evolution of information and communication technology, particularly the internet, has transformed communication into a digital format. The ubiquity of smartphones allows for diverse forms of communication, including engagement through social media. Applications like TikTok, favored among the younger demographic, serve as tools for legal professionals to construct information networks and convey legal knowledge in innovative ways. It is crucial to bear in mind that social media can have adverse effects concerning the spread of inaccurate legal information. Advocates can mitigate this impact by utilizing reputable platforms, delivering pertinent information, and collaborating with fellow legal experts to generate informative and reliable content. In the execution of their responsibilities, advocates are obligated to uphold the integrity and esteem of the profession, exercise prudence and ethical conduct in using social media to cultivate a professional image, and disseminate precise and beneficial legal information.